Intimate Partner Violence Against Women in Northwestern Botswana: The Maun Women's Study. (December 2018) - Barchi, Francis; Winter, Samantha; Dougherty, Danielle; Ramaphane, Peggie
Factors characterizing intimate partner violence (IPV) against women vary according to setting and must be understood in localized environments if effective interventions are to be identified. This 2009-2010 exploratory study in Maun, Botswana, used semistructured interviews to elicit information from 469 women about their experiences with IPV. Characteristics found to be important included suicide attempts, childhood exposure to familial violence, access to and control over certain tangible assets, number of children, household location and monthly income, controlling behavior by a partner, and alcohol consumption. Controlling behavior by a partner was the single greatest predictor of physical or psychological IPV.